The relevance of music therapy in paediatric and adolescent cancer patients: a scoping review - Román-Carlos Rod; Ana Noreña-Peña; Teresa Chafer-Bixquert; Alicia Lorenzo Vásquez; Javier González de Dios; Carmen Solano Ruiz (Taylor & Francis Group, 2022)
Background Music therapy is an emerging and useful methodology to improve the quality of life of children and adolescents with cancer. Objectives The objective of this scoping review was to examine the available literature and offer an analysis of the relevance of music therapy in paediatric oncology. We considered the effects of music therapy on children and adolescents with cancer as well as the perception of this population, their families, music therapists, and health professionals regarding the music therapy sessions conducted. Finally, we analysed the characteristics of the distinct types of music therapy interventions reported in the literature. Methods In this review, we applied the methodology proposed by Arksey and O'Malley. After performing a comprehensive academic literature database search, 522 articles were identified of which, 27 met the inclusion criteria. Results The results shed light on the use of music therapy as a means to facilitate self-esteem, to improve the physical, emotional, and cognitive aspects related to disease and, to a lesser extent, alleviate their physiological symptoms. Both children and adolescents with cancer were represented in the academic literature. The most prevalent findings described in these studies were the benefits of music therapy in terms of improved psychological well-being and social relationships in this population. Conclusions Music therapy interventions are generally well received, not only by children and adolescents with cancer, but also by their families, music therapists, and health professionals. Nevertheless, several gaps were identified in some of the studies we considered, including a lack of specificity regarding the results obtained or music therapy intervention methods used.